METODE BIMBINGAN DAN PENYULUHAN ISLAM DALAM MENINGKATKAN KESADARAN MASYARAKAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study used a type of qualitative descriptive research located in the village Parangloe District Biringbulu District Gowa. The research approach used is an approach to guidance and psychological approaches. Data collection methods are observations, in-depth interviews, and documentation. Data analysis is done with three phases: data reduction, data presentation and withdrawal of conclusions. The results of this research show that the technique of implementing guidance and counselling Islam in raising public awareness about the importance of education for children, there are 4 namely: a persuasive approach (inviting), giving advice, door to door techniques and techniques in using the method of lecture, namely: gentle technique, rational techniques and humour techniques. Supporting factors include the cooperation of Islamic counselling and village government, the availability of facilities and infrastructures in conducting Islamic counselling by the government, and the high enthusiasm of the community to follow the counselling Islam in raising public awareness about the importance of education while the inhibitory factor is, access road far and less conducive and busy community in farming.